Assessing perceived voice similarity using Multidimensional Scaling for the construction of voice parades - McDougall, Kirsty (International Journal of Speech, Language and the Law, 2013)
In recent years forensic phoneticians, in consultation with psychologists and law enforcement officers, have put considerable effort into devising and refining procedures for preparing and conducting fair voice parades. In England and Wales, a procedure for conducting a voice parade is outlined in a 2003 Home Office circular; this has been successfully implemented in a number of cases. These guidelines explain that a phonetician should examine the foil voice samples to ensure that the voices provide a fair comparison against the suspect, however, a formalised method for making this comparison is not offered. The present paper presents a method for assessing the degree of perceived (lay-listener judged) similarity among a group of voices for potential inclusion in a voice parade using Multidimensional Scaling.